Design portfolios : a recruiter's view - Smith, Mark W., 1956- (John Wiley & Sons, Inc., 2023)
"Portfolio design is central to making the transition from student to working professional. Hiring managers and recruiters spend as much time reviewing portfolios as they do interviewing applicants for positions. However, most curricula struggle to fully prepare students for the challenge of creating a portfolio and finding their first professional job, leaving students unsure how to organize and present their work. And most available resources are aimed at professionals rather than an inexperienced design student. Instead, this book offers easy-to-understand and constructive guidance that will be useful to a young designer with a project history that consists only of academic and internship work. Design Portfolios: A Recruiter's View provides a student-friendly guide, written from the perspective of a designer and design industry recruiter to what recruiters look for as they review a design portfolio. It shows students how to create a professional-quality portfolio that will get them to that all- important next step in the recruiting process--the interview. Using a unique plan of action, "The Four S's", the book presents an organizational mindset focused on the added value of telling your Story, revealing your Style, proclaiming your Substance, and Sharing your uniqueness effectively. In today's competitive market, a winning portfolio is much more than a simple accounting of digital skills and volumes of high-resolution graphics. This book shows students what recruiters really value and how to ensure their portfolios make the right impression"--